Бюджетне фінансування та банківське кредитування як інструменти розвитку агропромислового комплексу України - Качула, Світлана Валентинівна; Kachula, Svitlana; Гетель, В. В.; Hetel, V. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2025)
В статті розкрито актуальні питання фінансування АПК України, зокрема його залежність від державної підтримки та кредитних ресурсів. Досліджено основні механізми бюджетного фінансування аграрного сектору, також проаналізовано їх вплив на розвиток галузі. Окрему увагу приділено питанням кредитування АПК, зокрема державній програмі «Доступні кредити 5-7-9». Досліджено світовий досвід фінансування аграрного сектору та доведено, що успішні моделі підтримки агробізнесу у США, країнах ЄС та Канаді базуються на комплексному підході, що поєднує субсидії, страхові механізми, низьковідсоткове кредитування та податкові пільги. Встановлено, що підвищення ефективності фінансування аграрного сектору потребує комплексного підходу, який включає оптимізацію державного фінансування, розширення доступу до кредитів, залучення альтернативних джерел фінансування та спрощення бюрократичних процедур. Запропоновано рекомендації щодо вдосконалення системи державної підтримки та кредитування, які сприятимуть покращенню фінансового стану аграрних підприємств та забезпеченню стабільного розвитку агропромислового комплексу України. The article reveals the current issues of financing the agricultural sector of Ukraine, particularly its reliance on state support and credit resources. The main mechanisms of budget financing for the agricultural sector are studied, and their impact on the development of the industry is analyzed. It is established that the insufficient level of state support and the uneven distribution of funds between enterprises of different scales are significant obstacles to the sustainable development of agricultural production. Special attention is given to the issues of lending to the agricultural sector, in particular the state program "Affordable Loans 5-7-9." Its impact on the financial stability of enterprises is studied, and the main difficulties faced by agricultural producers when receiving financial assistance are also identified. It is established that high risks of insolvency, the complex procedure for issuing loans, and limited coverage of all segments of the agro-industrial complex remain key problems that complicate farmers' access to financial resources. The global experience of financing the agricultural sector is studied, and it has been demonstrated that successful models of agribusiness support in the USA, EU countries, and Canada are based on an integrated approach that combines subsidies, insurance mechanisms, low-interest lending, and tax breaks. The implementation of best global practices could help improve the financial sustainability of the Ukrainian agricultural sector. It has been shown that increasing the efficiency of financing the agricultural sector requires an integrated approach, including optimizing state financing, expanding access to loans, attracting alternative sources of financing, and simplifying bureaucratic procedures. Based on the research, the following recommendations have been formulated: optimizing state financing, increasing the availability of credit resources, attracting alternative sources of financing, and simplifying the procedures for obtaining financing. The implementation of these measures will ensure the stable development of Ukraine's agro-industrial complex, enhance its competitiveness in the global market, and contribute to the country's food security.
Budget financing and bank lending as tools for the development of Ukraine’s agro-industrial complex
Keywords: бюджетне фінансування; budget financing; кредитування; lending; агропромисловий комплекс; agro-industrial complex; державна підтримка; state support; фінансова політика; financial policy; державні програми; state programs; фінансові інструменти; financial instruments; державне регулювання; state regulation